Growth and ochratoxin a production by aspergillus species in coffee beans: impact of climate change and control using o3[Triatomic oxygen (ozone)] - Akbar, Asya Hussain (Cranfield University, 2015)
Coffee is an important beverage product in many parts of the world. During the production and processing of coffee the prevailing environmental factors and rate of drying can have a profound influence on colonisation by mycotoxigenic fungi and contamination with ochratoxin A (OTA). In Kuwait, coffee beans are imported from various parts of the world. The objectives of this project were to (a) to examine the diversity of mycotoxigenic fungi found in green and roasted coffee beans bought in the Kuwaiti market from different source countries and identify the dominant fungal populations, (b) to examine the ecology and ochratoxin A production by the ochratoxigenic strains and species isolated, (c) determine the effect of caffeine concentrations in vitro on growth and OTA production by strains from the Aspergillus section Circumdati and Section Niger groups, (d) evaluate the impact of interacting climate change factors (water activity (aw) x temperature x elevated CO2) on growth and OTA production in vitro and in situ, (e) determine the effect of aw and temperature interactions on ecology of strains of two new species, A. aculeatinus and A. sclerotiicarbonarius, isolated from coffee beans and (f) evaluate the efficacy of gaseous ozone (O3) for controlling OTA producing fungi and control of contamination in coffee beans after treatment and after storage. Cont/d.